2019
DOI: 10.12659/msm.913967
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Growth Factors Can Inhibit Photoaging Damage Induced by Ultraviolet A (UVA) on the Human Dermal Fibroblasts In Vitro

Abstract: Background Photoaging is the main cause of extrinsic skin aging. Daily exposure to ultraviolet A (UVA) accelerates the process of photoaging. The present study aimed to understand the role of concentrated growth factors (CGF) on UVA irradiated human skin cells. Material/Methods We isolated and subcultured normal human dermal fibroblasts (NHDFs) from 6 different human dorsal skins and established photoaging models of NHDFs irradiated by UVA to detect the influence of CGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…This is consistent with other studies regarding platelet-derived products that activate detoxifying enzymes by the overexpression of the antioxidant response element [31]. In fact, one of the major antioxidant enzymes, superoxide dismutase (SOD) with free radical scavenging activity has been shown to be upregulated after growth factor concentrate treatment following UV irradiation [32]. In this line, the use of epidermal growth factor has also shown to promote the expression of catalase in response to photodamage, which is an antioxidant enzyme prominently expressed in the stratum corneum of the skin [33].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies regarding platelet-derived products that activate detoxifying enzymes by the overexpression of the antioxidant response element [31]. In fact, one of the major antioxidant enzymes, superoxide dismutase (SOD) with free radical scavenging activity has been shown to be upregulated after growth factor concentrate treatment following UV irradiation [32]. In this line, the use of epidermal growth factor has also shown to promote the expression of catalase in response to photodamage, which is an antioxidant enzyme prominently expressed in the stratum corneum of the skin [33].…”
Section: Discussionsupporting
confidence: 90%
“…However, few studies have focused on the effects of CGF in repairing skin photoaging. In our previous study, we showed that CGF is capable of inhibiting UVA-induced photoaging of human dermal fibroblasts (HDFs) [ 19 ]; in the present study, we further elucidate the underlying mechanism for this CGF-mediated inhibition of UVA irradiation-induced aging.…”
Section: Introductionmentioning
confidence: 64%
“…Some studies have used a cell survival rate of 50% as the selection criterion for radiation dose [ 23 ]. Following literature and a previous study from our laboratory [ 19 ], we used 5, 10, 20, and 30 J/cm 2 of UVA to irradiate HDFs and screen the appropriate UVA irradiation dose. The results showed that the 24 h survival rate following irradiation with 20 J/cm 2 UVA was 64%, which met the requirements of the present study and thus was used as the UVA irradiation dose for the following experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study in this group compared CGF extract with other platelet concentrate including PRP, PRGF, and A‐PRF extract and reported more proliferation in PRP‐treated cells (Masuki et al, ). While in the study of Jun et al on CGF extracts (2, 5, 10, and 15%), a dose‐dependent manner in CGF groups was reported, study of Chen et al on the effects of 5, 10, 15, and 20% concentrations of CCM showed better effect of 5% CGF in comparison to other concentrations (Chen, Jiao, et al, ; Jun et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…Only one study in this group compared CGF extract with other platelet concentrate including PRP, PRGF, and A-PRF extract and reported more proliferation in PRP-treated cells(Masuki et al, 2016). While in the study of Jun et al on CGF extracts (2, 5, 10, and 15%), a dose-dependent manner in CGF groups was reported, study of Chen et al on the effects of 5, 10, 15, and 20% concentrations of CCM showed better effect of 5% CGF in comparison to other concentrations(Chen, Jiao, et al, 2019;Jun et al, 2018).3.4 | In vivo effect of CGFSince the introduction of CGF by Sacco in 2006, many studies have evaluated the osteoinductive and regenerative properties of CGF in clinical studies as case series, animal studies, or clinical trials. In this regard, with excluding case series (without a control group), 18 studies on bone regeneration and six studies on regeneration of other tissues are listed inTables 4 and 5.…”
mentioning
confidence: 95%